Clinical dilemma of selective caries removal in primary teeth: a scoping review - Asturini, Putri Ganesha; Fauziah, Eva (Journal of Stomatology, 2023)
Despite growing evidence supporting selective caries removal in managing deep caries, many practitioners still prefer to manage caries in a more invasive way. Although proven to be beneficial in preserving pulp vitality, there is a concern that leaving soft dentin behind will compromise the adhesion of dentin to restoration. This paper aimed to review the evidence supporting selective caries removal of deep dentin caries on primary teeth, and the arguments against the technique using a scoping review method. Various outcome parameters were applied to define and evaluate treatment success, including pulp and dentine responses, dentin micro-hardness, bacterial load of dentin under restoration, and restoration survival. A structured literature search of PubMed and Scopus databases was performed for relevant articles, using specific key words and based on a PICO-structured question: Does selective caries removal in carious deep dentin primary teeth show better results in terms of pulp exposure risk, restoration integrity, micro-hardness, and bacterial load of sub-restorative dentin compared with complete caries removal? Selective caries removal is a minimally invasive approach that evidently protects teeth from the risk of pulp exposure. Several aspects must be considered before making the clinical decision to selectively remove carious tissue in managing deep caries. All dental practitioners are expected to possess a thorough knowledge about pros and cons of selective caries removal to deliver evidence-based treatments to their patients.